Cent portraits de femmes des écoles française et anglaise (1909) : une réception de la peinture anglaise en France au prisme des genres - Julie Lageyre (Interfaces)
On April 22nd, 1909, the exhibition A Hundred Portraits of Women from the English and French Schools opened in the galleries of the Jeu de Paume, Paris. Organised by Armand Dayot (1851‑1934), it brought together the great masters of the French and English schools of the 18th century, through the theme of the female portrait. The event was a milestone in the reception of English painting in France, because of its scope, media exposure and critical acclaim. Within the frame of the exhibition, the study of female portraits accompanied a discussion about the characterization of an English art or a national school in England. Thus, the critical reception of the exhibition displays some interesting issues pertaining to the historiography of English painting as it was conceived in the 1900s in France, including the interaction between the history of the portrait, the art of female representation and the emergence of English art in the 18th century.